T-Cell Subsets and Interleukin-10 Levels Are Predictors of Severity and Mortality in COVID-19: A Systematic Review and Meta-Analysis - Alshammary, Amal F.; Alsughayyir, Jawaher M.; Alharbi, Khalid K.; Al-Sulaiman, Abdulrahman M.; Alshammary, Haifa F.; Alshammary, Heba F. (Frontiers in Medicine, 2022)
Background: A large number of COVID-19 patients reveal a marked decrease in their lymphocyte counts—a condition that translates clinically into the state of immunodepression, which appears common among these patients. Moreover, infected patients exhibit conflicting outcomes depending on their lymphocytopenia status, especially their T-cell counts: patients are more likely to recover or survive when lymphocytopenia is resolved, or otherwise develop severe complications that often lead to death. Similarly, IL-10 concentration has been found to be elevated in severity and mortality COVID-19 cases, and may be associated with the depression observed in T-cell counts. Therefore, it is critical for our understating of the disease course to identify the influence of T-cell subsets and IL-10 on COVID-19 severity and mortality groups. Accordingly, This systematic review and meta-analysis aims to measure T-cell subsets and IL-10 levels among COVID-19 patients. Understanding the underlying mechanisms of the immunodepression observed in COVID-19 and its consequences, may enable early identification of disease severity and reduction of overall mortality. Methods: A systematic search was conducted covering PubMed MEDLINE, Scopus, Web of Science, and EBSCO databases for journal articles published since December 2019 through 14 March 2021. In addition, we reviewed the bibliography of relevant reviews and the medRxiv preprint server for eligible studies. Our search covered published studies reporting laboratory parameters for T-cell subsets, (CD4) and (CD8), as well as IL-10, among confirmed COVID-19 patients. Five authors carried out the process of data screening, extraction, and quality assessment independently. The DerSimonian-Laird random-effect model was performed for this meta-analysis, and the standardized mean difference (SMD) and 95% confidence interval (CI) were calculated for each parameter. Results: 52 studies from 11 countries across 3 continents were included in this study. Compared with mild and survivor COVID-19 cases, severe and non-survivor cases exhibited a lower count of CD4/CD8 T-cells, and a higher level of IL-10. Conclusion: Collectively, our findings reveal that the level of CD4/CD8 T-cells, and IL-10, are reliable predictors of severity as well as mortality in COVID-19 infected patients. The study protocol is registered with the International Prospective Register of Systematic Reviews (PROSPERO); registration number CRD42020218918.